Energy justice and sustainability transitions in Mozambique - Broto, V; Baptista, I; Kirshner, J; Smith, S; Alves, S (Elsevier, 2018)
This paper advances the debate on energy justice by opening up a dialogue with postcolonial critiques of development. There is an imperative to develop energy justice theory fit to address the complex demands of a global energy transitions in poorer countries of the Global South. Delivering transformative change in contexts where energy systems are underdeveloped requires assessing energy justice principles from multiple situated perspectives, adjusted to the conditions that shape the possibilities for action. However, current theorizations of energy justice tend to build upon universalist notions of justice within a western tradition of thought which may not be entirely appropriate to deliver policy in postcolonial contexts. This paper offers a situated, particularistic analysis of energy transitions in Mozambique - a country which faces massive energy access challenges - to open a dialogue between theories of energy justice and postcolonial critiques. The paper focuses on three aspects of the energy transition occurring in Mozambique: the logics and impacts of off-grid innovation, the situated transformations occurring in the electricity network, and how transitions in energy fuels shape household experiences of energy access. The conclusion proposes two recommendations as key agendas for future research. The first is a methodological need for research methods to examine energy justice challenges from within specific, situated understandings of energy delivery. The second entails a call for emancipatory notions of energy justice that integrate concepts such as energy sovereignty at their core to emphasise the dimension of self-determination as a complementary aspect of energy justice.